Non-degradative ubiquitination in Smad-dependent TGF-β signaling - Tang Liu-Ya; Zhang Ying E (Cell & Bioscience, 2011)
Abstract Transforming growth factor-β (TGF-β) signaling is tightly regulated at the level of post-translational modification to transmit quantitative difference in ligand concentration into proportional transcriptional output. Ubiquitination is one such modification with several E3 ubiquitin ligases implicated in TGF-β signaling in marking crucial pathway components for proteasomal degradation. However, ubiquitination, particularly in the mono- or oligo-ubiquitin modifying form, is also known to regulate incorporation of substrate proteins into signaling complexes that involved in DNA repair, kinase activation, and endocytosis. This review focuses on recent advances in understanding the role of such non-degradative ubiquitination in TGF-β signaling.